Modelled Economic Analysis for Dacomitinib–A Cost Effectiveness Analysis in Treating Patients With EGFR-Mutation-Positive Non-Small Cell Lung Cancer in China - Yu, Yong-feng; Luan, Luan; Zhu, Fan-fan; Dong, Peng; Ma, Li-Heng; Li, Lan-ting; Gao, Lan; Lu, Shun (Frontiers in Oncology, 2021)
Objectives To establish the cost-effectiveness of dacomitinib compared to gefitinib from the Chinese healthcare system perspective. Patients Advanced non-small cell lung cancer harbouring epidermal growth factor receptor (EGFR) mutations Methods The partitioned survival analysis was undertaken to examine the cost-effectiveness of dacomitinib utilising individual patient data (IPD) from the pivotal randomised controlled trial (RCT) (ARCHER 1050). Three health states modelled were progression-free, post-progression and death. Parametric survival distributions were fitted to IPD against the Kaplan-Meier survival curves corresponding to progression-free survival (PFS) and overall survival (OS) outcomes by randomised groups. Costs included drug acquisition and administration, outpatient management (outpatient consultation and examinations), and best supportive care costs. Utility weights were sourced from pivotal trial and other published literature. The Incremental cost-effectiveness ratio (ICER) was calculated with costs and Quality-adjusted life years (QALYs) discounted at an annual rate of 5%. Both deterministic and probabilistic sensitivity analyses were undertaken. Results In the base case, dacomitinib (CNY 265,512 and 1.95 QALY) was associated with higher costs and QALY gains compared to gefitinib (CNY 247,048 and 1.61 QALYs), resulting in an ICER of CNY 58,947/QALY. Using the empirical WTP/QALY threshold, dacomitinib is a cost-effective treatment strategy for patients with EGFR-mutation-positive advanced NSCLC. The probabilistic sensitivity analysis suggested that dacomitinib had a 97% probability of being cost-effective. Conclusions Dacomitinib is a cost-effective treatment strategy in treating patients with EGFR-mutation-positive NSCLS from Chinese healthcare system perspective. The uncertainty around the cost-effectiveness of dacomitinib could be reduced if long-term survival data become available.